Best Answer

If the missing operational signs are pluses, that's 3b^2 + 4b + 1

Q: What does (b 1) (3b 1) equal?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================

6

(a+b)(3b+1)

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

If you mean 3b+9 = 12 then b equals 1

Related questions

3b2 - 3b = 3b(b - 1)

4b

2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

6

3ab - a - 3b2 + b = -3b2 + 3ab + b - a = -3b(b - a) + 1(b - a) = (1 - 3b)(b - a)

(a+b)(3b+1)

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

If you mean 3b+9 = 12 then b equals 1

Write down both equations (I'll label them (1) and (2)):(1) a = 3b - 4(2) a + b = 16Pass b to the left side of the equation (1):(1) a - 3b = -4(2) a + b = 16Multiply (1) by -1:(1) -a + 3b = 4(2) a + b = 16Add down both equations:-a + 3b + a + b = 4 + 164b = 20b = 5Replace b in (2):a + 5 = 16a = 11

(3b)5 = 243 b5The actual numerical value depends on the value of ' b ',and it changes instantly any time ' b ' changes.

1